Enhancing the Functional Properties of Tea Tree Oil: In Vitro Antimicrobial Activity and Microencapsulation Strategy - Manzanelli, Franco Antonio (2023)
In the context of addressing antimicrobial drug resistance in periocular infections, Tea TreeOil (TTO) has emerged as a promising therapeutic option. This study aimed to assess the efficacy ofTTO against bacterial strains isolated from ocular infections, with a particular focus on its ability toinhibit biofilm formation. Additionally, we designed and analyzed microcapsules containing TTOto overcome certain unfavorable physicochemical properties and enhance its inherent biologicalattributes. The quality of TTO was confirmed through rigorous analysis using GC-MS and UV-Vistechniques. Our agar diffusion assay demonstrated the effectiveness of Tea Tree Oil (TTO) againstocular bacterial strains, including Corynebacterium spp., coagulase-negative Staphylococcus spp.,and Staphylococcus aureus, as well as a reference strain of Staphylococcus aureus (ATCC 25923). Notably, the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC)for all tested microorganisms were found to be 0.2% and 0.4%, respectively, with the exception ofCorynebacterium spp., which exhibited resistance to TTO. Furthermore, TTO exhibited a substantial reduction in biofilm biomass, ranging from 30% to 70%, as determined by the MTT method.Through the spray-drying technique, we successfully prepared two TTO-containing formulationswith high encapsulation yields (80–85%), microencapsulation efficiency (90–95%), and embeddingrates (approximately 40%). These formulations yielded microcapsules with diameters of 6–12 µm,as determined by laser scattering particle size distribution analysis, and exhibited regular, sphericalmorphologies under scanning electron microscopy. Importantly, UV-Vis analysis post-encapsulationconfirmed the presence of TTO within the capsules, with preserved antioxidant and antimicrobialactivities. In summary, our findings underscore the substantial therapeutic potential of TTO and itsmicrocapsules for treating ocular infections.